2021
DOI: 10.1038/s41598-021-85239-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biochar on the content of carbon and the chemical transformations of fallow and grassland humic acids

Abstract: There is limited information regarding the effect of biochar (BioC) on the fertility of fallow and grassland soils, as well as on the properties of their humic acids (HAs). The objective of this study was to evaluate with a 3-year field experiment the influence of BioC on the organic matter (OM) in Haplic Luvisol. BioC (obtained via wood waste pyrolysis at 650 °C) was applied to the soil of subplots under fallow and grassland at doses of 0, 1, 2 and 3 kg m−2. The soil samples were collected eight times. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
1
5
0
1
Order By: Relevance
“…Results for the AL soil showed that the value of this parameter increased significantly in the T2 and T3 due to the addition of fungal or bacterial strains without NPK, in comparison to HAs from soil without microorganisms. This direction of ∆lgK change indicated a decrease in the degree of humification [10]. A similar trend was also supported by our fluorescence studies.…”
Section: Changes In Degree Of Humification Of Has Derived From Soils With Mineral Fertilization and Fungal And Bacterial Strains Based Onsupporting
confidence: 90%
See 1 more Smart Citation
“…Results for the AL soil showed that the value of this parameter increased significantly in the T2 and T3 due to the addition of fungal or bacterial strains without NPK, in comparison to HAs from soil without microorganisms. This direction of ∆lgK change indicated a decrease in the degree of humification [10]. A similar trend was also supported by our fluorescence studies.…”
Section: Changes In Degree Of Humification Of Has Derived From Soils With Mineral Fertilization and Fungal And Bacterial Strains Based Onsupporting
confidence: 90%
“…As HAs comprise a fraction of humic substances intermediate between fully soluble fulvic acids and non-soluble humins [10], they are extremely interesting from a chemical point of view. They undergo constant biochemical changes, the mechanisms and dynamics of which remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The plant works on the principle of conductive pyrolysis. Designing equipment where waste is converted into coal seems to be a complex task that requires taking into account many factors [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the positive effect of biochar on carbon sequestration [21]; CO 2 , N 2 O, and CH 4 emission reduction [24]; toxic metals remediation [18]; or antibiotic, pesticide, or other personal care products' immobilization [25]. However, not all results show a similar scale or even a similar direction of biochar addition effects [26][27][28]. For example, Brewer et al [29] indicated an example of biochar with an abundance of nanopores being not well accessible to plants.…”
Section: Introductionmentioning
confidence: 99%